Controle estratégico de Amblyomma cajennense (Fabricius, 1787) (Acari: Ixodidae) e Anocentor nitens (Neumann, 1897) (Acari ixodidae) em eqüinos, Minas Gerais, Brasil. - Arildo Pinto da Cunha (2006)
The aim of this study was to evaluate the application of a strategic control program of Amblyomma cajennense in equines, in the city of Palma, MG. Before the implantation of the program the parasitic loads of the A. cajennense and Anocentor nitens were observed, monthly, in the period from October of 2003 to March of 2004, in the same period of the following year the comparative analyses were carried. The acaricide treatments were carried to each seven days and divided in two batteries: the first one beginning in April of 2004, composed of eight treatments and second beginning in July of 2004, composed of five treatments, respectively, aiming to reach the larvae and nymphs of the A. cajennense. The chemical base used was pyrethroid - cypermethrin 0.015%, to bathe the equines. Clinical and hematological aspects (hemogram and serum biochemical) of the equines were analyzed before the control program. Also the effect of the program destined to the control of the A. cajennense on the population of A. nitens was observed. After the control program had a reduction of 44.85% of adults A. cajennense of October of 2004 to March 2005, and 59.74%, in February and March of 2005. The results of the clinical and hematological examinations of the equines had not evidenced alterations undesirable, but the improvement in some hemogram parameters. However the acaricide treatments had not determined significant reduction of the parasitic load of A. nitens in the equines. The control program revealed effective and safe for the control of the A. cajennense in the equines. However, it was not possible to carry through all the stages of the initial planning, once the study was carried on a commercial property, searched to define some critical points for the implantation of this type of technology in field situations. The interference was evidenced of the management model and structure of the agricultural company with the operational and technical aspects of the proposal of control of the tick, factors that can be determinant in the degree of success of the sanitary control. The permanence of the levels of infestation for A. nitens can be by no application of acaricide in nasal diverticulums of the equines, since this is an important site of parasitism of A. nitens in equines, however theres no compatible methods or acaricide formulations with the particularities of this anatomical structure.